Analysis defeat for the couple Herman Deru and Maphilinda Syahrial Oesman in the general election of regional heads of South Sumatra in 2013 - tejamurti, wisnu; utomo, susilo; herawati, nunik retno (Journal of Politic and Government Studies, 2016)
In 2013, the Provincial Election Commission to hold elections in SouthSumatra. In these elections, there are two candidates for the strongest candidate isa pair Herman Deru - Maphilinda Syahrial Oesman and partner Alex Noerdin -Ishak Mekki. There are several organizations surveyed stated that couples HermanDeru - Maphilinda Syahrial Oesman get the most votes, it is because AlexNoerdin leave the task as governor of South Sumatra and running for governor ofJakarta, not only that the issue of corruption by Alex Noerdin in developmenthouse athelete construction of a multipurpose building South Sumatra province.Herman Deru shook the first Regent of Ogan Komering Ulu Timur, andMaphilinda Syahrial Oesman is the wife of former South Sumatra Governorappointed by Herman Deru to accompany the elections in South Sumatra in 2013.Alex Noerdin governor of South Sumatra in the first period were runagain in the elections of South Sumatra in 2013 and is a former Regent of MusiBanyuasin for two periods, Alex Noerdin pointed Ishak Mekki as a deputy whohad served as Regent of Ogan Komering Ilir during two periods.South Sumatra at the General Election in 2013, the pair Alex Noerdinand Ishak Mekki guilty of corruption of the budget used for campaign purposes inseveral regencies / municipalities , despite experiencing negative issues and terevidence of corruption, the couple still won the elections of regional heads ofSouth Sumatra.The purpose of this study to determine the factors defeat Herman Deruand Maphilinda Syahrial Oesman. In order to strengthen and achieve theobjectives of this study, researchers used a qualitative descriptive approach.Extracting data through interviews with a successful team. Based on research,there are three theories to gain a whopping factor Herman roar and MaphilindaSyahrial Oesman that election, political strategy, figures, and successful team.Based on the research results , the researcher recommends that : doingthe sportive of competition and does not do character assassinations between thecandidates , the Commission and the Election Supervisory Committee must actdecisively against negative practices conducted by candidates , their improvementeducational background of candidates , and the candidates should be moreintroduce themselves and multiply achievements to be more widely known .